Analysis of Grade 3 Textbook Our Wondrous World with Special Reference to NEP 2020 and NCF-SE 2023: NEP 2020 - Sharma, Shesh Kumar (JOURNAL OF INDIAN EDUCATION, 2026)
This study concluded a content analysis of the NCERT Grade 3 Textbook ‘Our Wondrous World’, that is, ‘The World Around Us’. Textbook promotes holistic development, incorporating indigenous culture to sustain Indian identities in our young learners. Through content analysis, it was evident that ‘Our Wondrous World’ employs a multidisciplinary approach, featuring vibrant illustrations and engaging exercises. Further, the content textbook fosters a deeper understanding of the Indian Knowledge System, aiming to acquire Indian rootedness and ideal character formation in learners. Content of the textbook has been presented using reflective, inquiry-based, theme-based, activity-based, toy-based, and play-based pedagogy by citing examples in the local context. The textbook acts as a learning resource in promoting an effective learning environment among learners. The present paper discusses about analysis of Grade 3 textbook ‘Our Wondrous World’ with special reference to NEP 2020 and NCF-SE 2023